Empirical and analytical subaltern space?: ashrams, brothels and trafficking in colonial Delhi - Legg, Stephen (Taylor & Francis, 2016)
In this paper, I will engage with Gayatri Spivak’s writings on the figure of the subaltern, focusing on a recurrent tension in her writings, and in readings of them. The tension is between two seemingly contradictory definitions of the subaltern. One, more empirical definition, has featured in Spivak’s writings for over 25 years and identifies the subaltern as the non-elite, the immobile or the figure beyond the reach of the state. Against this more empirical definition comes the famous analytical definition of the subaltern as he or she that ‘cannot speak’, being defined by their inaccessibility in the archive, as broadly conceived. This paper will argue that these two interconnected definitions have their respective forms of space, which suggest and demand different methodologies. I will suggest that an over-emphasis on the analytical definition has led to an over-cautious approach to subaltern spaces, neglecting the compulsion to attempt to find and say something about subaltern spaces, as suggested by Spivak. The paper demonstrates this approach through the examination of a report into abuse of women in some of Delhi’s ashrams in the 1930s, such as to suggest how we can use studies of empirically archived subaltern space to think about the analytically subaltern spaces that must always be beyond exploration.